Eco-friendly management of mustard aphid, Lipaphis erysimi Kalt.: Eco-friendly management of mustard aphid, Lipaphis erysimi Kalt. - D K SINGH; S K VERMA; MAHAK SINGH; NALINI TIWARI (Journal of Oilseeds Research, 2023)
A field trial was conducted at Oilseed Farm, C S Azad University of Agriculture & Technology, Kanpur. The trial was laid out in RBD with three replications using mustard cultivars Varuna. Seven insecticides viz. NSKE@5%, Neem leaf extract@ 5%, Neem oil 2%, Eucalyptus leaf extract 5%, Fennel leaf extract 5%, Dimethoate 30EC @ 1ml/liter and Thiamethoxam 25WG @ 0.2gm/liter with second spray of each treatment after 15 days of first spray were evaluated. Thiamethoxam 25WG @ 0.2gm/liter followed by its second spray after 15 days of first spray was most effective treatments against mustard aphid followed by Dimethoate 30EC @ 1ml/liter followed by its second spray after 15days of first spray. The highest seed yield (18.73 q/ha.) was obtained with Thiamethoxam 25WG @ 0.2gm/liter followed by its second spray after 15 days of first spray which was at par with NSKE@5% followed by its second spray after 15days of first spray (16.83 q/ha.). The incremental Benefit Cost Ratio (1:40:63) was also highest with Thiamethoxam 25WG @ 0.2gm/liter followed by its second spray after 15 days of first spray.